2013
DOI: 10.1073/pnas.1221841110
|View full text |Cite
|
Sign up to set email alerts
|

Targeting chronic lymphocytic leukemia cells with a humanized monoclonal antibody specific for CD44

Abstract: Chronic lymphocytic leukemia (CLL) cells express high levels of CD44, a cell-surface glycoprotein receptor for hyaluronic acid. We found that a humanized mAb specific for CD44 (RG7356) was directly cytotoxic for leukemia B cells, but had little effect on normal B cells. Moreover, RG7356 could induce CLL cells that expressed the zeta-associated protein of 70 kDa (ZAP-70) to undergo caspasedependent apoptosis, independent of complement or cytotoxic effector cells. The cytotoxic effect of this mAb was not mitigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 39 publications
(33 reference statements)
0
59
0
1
Order By: Relevance
“…For example, CD44 is a critical factor in chronic lymphocytic leukemia disease progression, and the use of antibodies specifically targeting CD44 leads to complete clearance of engrafted leukemic cells in xenograft mouse models (43,44). However, examining the CD44 expression profile from erythroid gene expression datasets indicates that, unlike in mice where Cd44 expression decreases upon maturation, human red cells highly express CD44, an observation that we substantiated using flow cytometric analysis of mature red blood cells (Fig.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, CD44 is a critical factor in chronic lymphocytic leukemia disease progression, and the use of antibodies specifically targeting CD44 leads to complete clearance of engrafted leukemic cells in xenograft mouse models (43,44). However, examining the CD44 expression profile from erythroid gene expression datasets indicates that, unlike in mice where Cd44 expression decreases upon maturation, human red cells highly express CD44, an observation that we substantiated using flow cytometric analysis of mature red blood cells (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…2B). Therefore, caution needs to be applied to translate such models between species: CD44 antibodies might be readily absorbed by mature human red blood cells in the circulation, decreasing the effectiveness of such treatments, which could not be identified in preclinical xenograft models (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…IM7 is a murine monoclonal antibody specifically targeting CD44, which has a confirmed inhibitory effect on tumor growth. Zhang et al (87) reported that RG7356, a humanized antibody against CD44, could induce apoptosis of chronic lymphocytic leukemia cells.…”
Section: Lcsc Surface Markers and Targeted Therapiesmentioning
confidence: 99%
“…CD44 has been identified as a key regulator of AML LSC with no documented effect on engrafted normal hematopoietic cells derived from cord blood or human bone marrow 135 . Very recently, a humanized monoclonal antibody specific for CD44 that targets and directly kills chronic lymphocytic leukemia cells, was identified 136 . The cytotoxic effect of anti-CD44 treatment was not mitigated by interaction with mesenchymal stromal cells or hyaluronic acid.…”
Section: Cd44mentioning
confidence: 99%